2020
DOI: 10.1101/2020.10.01.323253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessingin vivomutation frequencies and creating a high-resolution genome-wide map of fitness costs of Hepatitis C virus

Abstract: Studying in vivo fitness costs of mutations in viruses provides important insights into their evolutionary dynamics, which can help decipher how they adapt to host immune systems and develop drug resistance. However, studying fitness costs in natural populations is difficult, and is often conducted in vitro where evolutionary dynamics differ from in vivo. We aimed to understand in vivo fitness costs of mutations in Hepatitis C virus using next generation sequencing data. Hepatitis C virus is a positive-sense s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Our study confirmed that results from our previous study on subtype 1a [ 19 ] generally also hold for subtypes 1b and 3a. Genetic diversity is the lowest in the 5′ UTR (the 3′ UTR was not included in our study) and, by far, the highest in the Hyper Variable Region 1 (HVR1), which is part of the E2 gene.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study confirmed that results from our previous study on subtype 1a [ 19 ] generally also hold for subtypes 1b and 3a. Genetic diversity is the lowest in the 5′ UTR (the 3′ UTR was not included in our study) and, by far, the highest in the Hyper Variable Region 1 (HVR1), which is part of the E2 gene.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple factors simultaneously drive and constrain mutation frequencies, and these effects were explored using beta-regression models to understand the driving force of similarities and differences in mutation patterns across subtypes. We explored the effects of ancestral nucleotide, mutation type (synonymous/nonsynonymous, whether a mutation creates a CpG-site or not or causes a drastic amino acid (AA) change or not), location in the genome, and interactions of these factors, as they were known to shape mutation patterns in HCV [ 19 ]. The best-fit model included a total of 15 factors ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations